ANALYSIS OF BASIC SKILLS OF SEPAK SILA IN SEPAK TAKRAW GAMES - Ibrahim, Muhammad Bagus Ragil; Topo Yono (UNIVERSITAS NEGERI JAKARTA POSTGRADUATE OF PHYSICAL EDUCATION DEPARTMENTS, 2025)
This study aims to determine the skill level of basic sepak takraw techniques among sepak takraw athletes at SD Negeri Gunungmalang 03. The research employs a descriptive quantitative method. The participants consist of five students enrolled in the school's sepak takraw extracurricular program, selected based on availability during the test. The sampling method used is purposive sampling. Data collection was conducted through a football skills test, assessing the frequency of football skills performed within one minute over three trials. Data analysis was carried out using descriptive statistics in the form of percentages. The results indicate that the majority of participants demonstrated a